Red pulp macrophages clear parasites, while marginal metallophilic and marginal zone macrophages support CD4+ T cell activation during Plasmodium yoelii infection - Julia Falkenstein; Anne Ninnemann; Matthias Hose; Abdelrahman Elwy; Karl S. Lang; Kai Matuschewski; Jan Buer; Astrid M. Westendorf; Wiebke Hansen (Frontiers in Immunology)
Malaria, caused by the parasite Plasmodium spp., remains the most prevalent and dangerous vector-borne infectious disease worldwide. Effective pathogen clearance during malaria hinges on the interplay between adaptive and innate immune responses, especially on T cells, B cells, antigen-presenting cells (APCs) and IFNγ response. In a previous study, we demonstrated that dendritic cell (DC) depletion resulted in impaired T cell responses. However, substantial CD4+ and CD8+ T cell activation was still detectable, suggesting that other APCs compensate for the lack of DCs. In the present study, we report an increase in splenic marginal zone macrophages (MZMΦ), and marginal metallophilic macrophages (MMMΦ) with an altered cytokine profile in DC-deficient mice upon P. yoelii infection. Ablation of macrophages by clodronate liposome (CL) application resulted in partially reduced T cell activation, which correlated with elevated parasitemia. To further elucidate the specific role of splenic macrophage subsets we studied P. yoelli infections in two transgenic C57BL/6 mouse lines. Treatment of CD169DTR mice with diphtheriatoxin (DT) efficiently depleted MMMΦ and MZMΦ, resulting in reduced IFNγ production by CD4+ T cells in P. yoelii-infected mice, though parasitemia progression was not modulated. In marked contrast, specific red pulp macrophages (RPMΦ) depletion in SpiCflox/flox x vav1cre mice resulted in elevated parasitemia. In conclusion, our data provide evidence that splenic macrophages located in or at the marginal zone contribute to CD4+ T cell activation, and that RPMΦs are indispensable for clearing of infected red blood cells (iRBCs) during P. yoelii infection.